Low-mass Stars: Their Protoplanetary Disk Lifetime Distribution - Susanne Pfalzner; Furkan Dincer (The Astrophysical Journal, 2024)
While most protoplanetary disks lose their gas within less than 10 Myr, individual disk lifetimes vary from <1 Myr to ≫20 Myr, with some disks existing for 40 Myr. Mean disk half-lifetimes hide this diversity; only a so-far nonexisting disk lifetime distribution could capture this fact. The benefit of a disk lifetime distribution would be twofold. First, it would provide a stringent test on disk evolution theories. Second, it could function as an input for planet formation models. Here, we derive such a disk lifetime distribution. We heuristically test different standard distribution forms for their ability to account for the observed disk fractions at certain ages. We here concentrate on the distribution for low-mass stars (spectral types M3.7–M6, M _s ≈ 0.1–0.24 M _⊙ ) because disk lifetimes depend on stellar mass. A Weibull-type distribution ( k = 1.78, λ = 9.15) describes the observational data if all stars have a disk at a cluster age t _c = 0. However, a better match exists for lower initial disk fractions. For f ( t =0) = 0.65, a Weibull distribution ( k = 2.34, λ = 11.22) and a Gaussian distribution ( σ = 9.52, μ = 9.52) fit the data similarly well. All distributions have in common that they are wide, and most disks are dissipated at ages >5 Myr. The next challenge is to quantitatively link the diversity of disk lifetimes to the diversity in planets.